Assessing the perceived brand image of TM and customer satisfaction level at TMpoint in Kuching / Abdurahim Dawi ... [et al.]. - Dawi, Abdurahim; Hj Khalit, Nazarihan (2008)
The objectives are to determine TM Brand's image and compare it with other brand in the market. This project is also to determine the level of customers' satisfaction at TMpoint. There are 2 parts of the study involving the general public at large in Kuching and TM's customers patronising TMpoint. For the first part, the six core attributes, namely Innovativeness, Credibility of Image, Understanding Customer, Quality, Value for Money and Trustworthiness adopted from the Reader's Digest Trusted Brand Survey and additional attribute of Reliability were used to measure the perceived brand image of TM Brand. Based on the literature reviews, the items describing these core attributes are identified and a focus group consisting of experienced managers from various industries is conducted. From here the questionnaires are prepared and given to the respondents.